1994
DOI: 10.1093/jnci/86.6.441
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Studies of Taxol as a Radiation Sensitizer in Human Tumor Cells

Abstract: Paclitaxel can radiosensitize to a modest degree some, but not all, human cell lines by a mechanism that requires the production of a G2/M cell cycle block. Additional studies are needed to define more clearly the mechanism by which paclitaxel radiosensitizes cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
99
1
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(104 citation statements)
references
References 0 publications
2
99
1
2
Order By: Relevance
“…There are reports suggesting, that supraadditive interaction could be seen without mitotic arrest; 4,5 furthermore, even if mitotic arrest occurs, the enhancement in radioresponse is not necessarily the result of this. 6,9 When malignant tumors are exposed to paclitaxel followed by radiation, the resulting growth inhibition or delay is achieved by several mechanisms on both cellular and molecular levels. When paclitaxel is combined with radiation, the growth inhibition is expected to be potentiated at least by paclitaxel-induced inhibition of sublethal repair and repopulation, as well as the apoptosis-enabled reoxygenation when in vivo models are used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports suggesting, that supraadditive interaction could be seen without mitotic arrest; 4,5 furthermore, even if mitotic arrest occurs, the enhancement in radioresponse is not necessarily the result of this. 6,9 When malignant tumors are exposed to paclitaxel followed by radiation, the resulting growth inhibition or delay is achieved by several mechanisms on both cellular and molecular levels. When paclitaxel is combined with radiation, the growth inhibition is expected to be potentiated at least by paclitaxel-induced inhibition of sublethal repair and repopulation, as well as the apoptosis-enabled reoxygenation when in vivo models are used.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained with this combined treatment modality in vitro seem to be somewhat less than has been expected. Both supraadditive [3][4][5][6] and additive [7][8][9][10] results have been reported in a variety of malignant cell lines, but subadditive interaction has also been demonstrated in vitro. 11,12 Contradictory outcomes in cytotoxic studies on the mechanism of action of paclitaxel have thrown doubt on the accumulation in G 2 /M being the main reason for the antitumor activity of paclitaxel.…”
mentioning
confidence: 99%
“…In the literature, it was demonstrated that vincristine-resistant RPMI-8226 and U-266 MM cells did not show any cross-resistance when exposed to ␥-radiation and vincristine-resistant sublines were radiosensitive (Mutlu et al, 2011). In addition, the results of other studies showed that paclitaxel enhanced tumor radio response (Choy et al, 1993;Klappe et al, 2004;Liebmann et al, 1994;Milas et al, 1994). Both vincristine and paclitaxel are chemotherapeutic agents that stabilize microtubule activity and arrest cells in G 2 -M phase.…”
Section: Cross-resistance To Radiationmentioning
confidence: 98%
“…As mitotic cells with double strand breaks will lose genetic material following cell division, irradiation of MSA-treated, transiently arrested late G2-/M-phasecells will result in genomic instability and eventually mitotic catastrophe. (35,(41)(42)(43)(44)(45) This implies that the therapeutic efficacy of the combined treatment modality strongly depends on the innate cellular drug sensitivity and in particular on the combination scheduling. Indeed, effects ranging from supra-additive interactions (Figure 3 A similar effect has also been described for synchronized HeLa cells, in which docetaxel resulted in a S-phase specific (and hence radioresistant) cell killing.…”
Section: Rationale For the Combined Use Of Irradiation And Cytotoxic mentioning
confidence: 99%